Longman preparation series for the new TOEIC® test : - Lougheed, Lin (Pearson Education, 2013)
Longman Preparation Series for the New TOEIC® Test: Introductory Course, Fourth Edition, gives beginning through low-intermediate students the skills, strategy, practice, and confidence they need to increase their scores on the new TOEIC® test. Ideal for a TOEIC® test preparation course or for self-study, the Introductory Course is intended for students who achieve TOEIC® test scores from 200 to 500.